Cytotoxic Coumarins from Mammea harmandii - Vichai Reutrakul (2018)
Two new naturally occurring coumarins, isomesuol (1) and mammearin A (2), together with nine known Mammea coumarins 3-11 were isolated from the EtOAc extract of the leaves and twigs of Mammea harmandii. Coumarins 1, 3 and 4 showed cytotoxicity against a panel of mammalian cancer cell lines. Their structures were determined by spectroscopic methods. The assignments of13C-NMR signals of isomesuol (1), which was isolated for the first time as a natural product, have been revised.